Divergent taxonomic responses of below-ground microbial communities to silicate fertilizer and biofertilizer amendments in two rice ecotypes - Mallano, Ali Inayat; Zhao, Xianlin; Wang, Haifeng; Jiang, Guangpin; Sun, Botong; Huang, Chao (Frontiers in Agronomy, 2022)
Abstract Using silicate fertilizer and bacterial inoculum as biofertilizer is significant for increasing soil silicon (Si) availability and rice agronomic performance. To use microbial technology for sustainable agriculture, it is crucial to have a deeper knowledge of how microbial populations shift among the plant hosts and related compartments, as well as how they respond to various fertilization models. In this study, the effects of silicate fertilizer, a single bacterial strain Bacillus mucilagniosis as biofertilizer, and their integrated application on soil physiochemical properties and soil microbiota structure, composition, and diversity in two eco-geographically diverse races (Indica and Japonica rice) were evaluated. Plant compartment, cultivar type, and fertilizer treatments contributed to microbiome variation. Indica and Japonica harbor different root microbiota; notably, taxa enriched in the rhizosphere soil were more diverse than in the root. Bacterial genera Leptonema, Azospira, Aquabacterium, Fluviicola, Aquabacterium, Leptonema, and fungal genera Metarhizium, Malassezia, and Cladosporium all were found in the rice core microbiome. Both silicate and biofertilizer applications increase the relative abundance of Betaproteobacteria, Deltaproteobacteria, and Actinobacteria, while suppressing fungal pathogens Alternaria and Fusarium. Silicate and bacterial inoculum applications increased the soil pH, available silicon content (ASi), available phosphorous (AP), available potassium (AK), and organic carbon (OC), while reduced the Total nitrogen (N). These changes were also associated with major bacterial phyla Spirochaetes, Bacteroidetes, Actinobacteria, and Proteobacteria, except for Acidobacteria, and fungal phyla Ascomycota, Mortierellomycota and unassigned fungi. Several treatment-specific biomarkers were revealed through Linear discriminant analysis effect size (LEfSe) analysis. In conclusion, the change in the structure of root-associated communities driven by plant compartment and genetics suggests dynamic interactions in the host plant microbiome. Short-term silicate and biofertilizer amendments improved soil physiochemical status and altered bacterial and saprotrophic fungal communities, which have important implications for sustainable rice production.